If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying c = 2b + 2ax Reorder the terms: c = 2ax + 2b Solving c = 2ax + 2b Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Simplifying c = 2ax + 2b
| x^2+11x+59=-3x+10 | | .16-.01(x+3)=-.03(1-x) | | -5x-8(1+7)=-8 | | x^2-3x-18=-6-8 | | x^3=11x-3x^2 | | -5x-81(1+7x)=-8 | | ln(3x)=0 | | x^2-8x+8=-4 | | x^2-18x+85=4 | | x+4a+11ax=0 | | (2x^3-6x^2-2x^4)+(2-4x+7x^2)+(5x^2+6-5x^4)= | | x^2+16x+12=9x | | 4a+x+11ax=0 | | x^2+4x=x+4 | | 2x+8-3y=8x | | x^2-20x+80=-x-10 | | 5(6x-4)=33 | | X(x+2)=(-x-4) | | -2z-2z=6z+1-2z | | x^2+4x+2=9x-4 | | x^2+4x+2=9-4 | | 5x^2+8x-14=40-31x | | 3?(-8)= | | Log(4)(3x-5)=3 | | -6x+7x^2-13= | | 5x^2+30x+29=0 | | -4y+8=-2(4y+4) | | x^2-14x=-7x-6 | | 2In(3x)=8 | | 15x-4+4x+5+65=180 | | x^2-23x+72=-6x | | 5g=2g+12 |